1992
DOI: 10.1038/356706a0
|View full text |Cite
|
Sign up to set email alerts
|

Antiquity of clonal salamander lineages revealed by mitochondrial DNA

Abstract: The existence of clonally reproducing vertebrates has often served as a foil in attempts to explain the near-ubiquity of sexual reproduction in eukaryotes, but the absence of recombination, with its attendant limitation of new genotypes to those produced through mutations, restricts the adaptive ability of clonal organisms. It has been argued, therefore, that clonal vertebrate taxa have short lifespans. Variation in mitochondrial DNA (mtDNA) within clonal populations is interpreted instead as reflecting multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
73
2

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 11 publications
4
73
2
Order By: Relevance
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, comparative studies on mitochondrial and nuclear genome sequences in unisexual vertebrates suggested that the unisexual biotypes would seem to be genuinely older than the predicted age. Unisexual Ambystoma salamanders had been considered as the most ancient unisexual lineage in vertebrates [12], because the divergence time with the related sexual species was estimated to be about 2.4 to 5 million years ago [13][14][15]. Parthenogenetic geckos (Heteronotia binoei) were revealed to have 2 distinct maternal lineages by mtDNA sequences [16], and their divergence time was estimated to be about 50000 to 730000 years ago [17].…”
mentioning
confidence: 99%
“…A small number of asexual, parthenogenetic salamanders in North America have persisted for millions of years (15). These lineages are all-female but require sperm from males of a different, sexual species to initiate egg division and embryogenesis.…”
Section: Asexualitymentioning
confidence: 99%